Peran Perempuan Dalam Aktvitas Pariwisata di Desa Wisata Celuk, Kabupaten Gianyar - Pradita Ayudia, Dewa Ayu Ratih; Winarya , I Wayan Sukma; Lilasari , Luh Nyoman Tri (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2024)
This research aims to determine the role of women in tourism activities in Celuk Tourism Village, Gianyar Regency. The qualitative method with a descriptive approach was method used in this research and in terms of data collection, applied mostly in interviews and observation. The results of this research show that the role of women in tourism activities in Celuk Tourism Village plays a role in three things, namely: (1) The role of women in tourist attractions such as silver crafts and tubing, (2) The role of women in managing tourist facilities such as silver galleries, accommodation and restaurants, and (3) The role of women in tourism organizations. Challenges for women in roles include a lack of skills in technology, the younger generation of women who are less interested in silversmithing and multiple roles. To overcome this problem, efforts have been made by the Gianyar Regency Tourism Office by providing education and training as well as socializing the village's potential